2011
DOI: 10.1002/jez.b.21400
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among hemocytes, tunic cells, germ cells, and accessory cells in the colonial ascidian Botryllus schlosseri

Abstract: Monoclonal antibodies were raised against hemocytes of the colonial ascidian Botryllus schlosseri as possible tools to study hemocyte differentiation. In this species, blood cells are involved in various biological functions, such as immunosurveillance, encapsulation of foreign bodies, metal accumulation, and allorecognition. The latter process drives the fusion or rejection of contacting colonies, according to whether they do or do not share at least one allele at the fusibility/histocompatibility (Fu/HC) loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 86 publications
4
6
0
Order By: Relevance
“…The identified cell types are compatible with previous reports in this species (Cima et al, 2002), comparable to those in other ascidians (Cima et al, 2014) and in particular to those of the same family (Styelidae; Ballarin and Kawamura, 2009;de Barros et al, 2009;Gutierrez and Brown, 2017). Notably, while granular cells appear to be absent from other botryllid species (Hirose et al, 2003;Ballarin et al, 2011), they have been identified in Styela plicata (de Barros et al, 2009), Symplegma brakenhiemli (Gutierrez and Brown, 2017) and even in Thalia democratica (Cima et al, 2014). Their presence in more distant species of ascidians suggests either a loss in botryllids that did not affect B. leachii or that their visual characteristics are not observable in these botryllids.…”
Section: Hemolymph Composition In Styelidaesupporting
confidence: 91%
“…The identified cell types are compatible with previous reports in this species (Cima et al, 2002), comparable to those in other ascidians (Cima et al, 2014) and in particular to those of the same family (Styelidae; Ballarin and Kawamura, 2009;de Barros et al, 2009;Gutierrez and Brown, 2017). Notably, while granular cells appear to be absent from other botryllid species (Hirose et al, 2003;Ballarin et al, 2011), they have been identified in Styela plicata (de Barros et al, 2009), Symplegma brakenhiemli (Gutierrez and Brown, 2017) and even in Thalia democratica (Cima et al, 2014). Their presence in more distant species of ascidians suggests either a loss in botryllids that did not affect B. leachii or that their visual characteristics are not observable in these botryllids.…”
Section: Hemolymph Composition In Styelidaesupporting
confidence: 91%
“…Studies on self-and cross-fertilization declined in the 1970s but still offered cues regarding the successive investigations on the reproduction of B. schlosseri, primarily addressing the study of the morphology of the gonads and gametes (Burighel and Martinucci, 2000;Burighel et al, 1982;Manni et al, 1993Manni et al, , 1994Sabbadin and Zaniolo, 1979), the success of fertilization in relation to population density and sperm release (Johnson and Yund, 2004;Phillippi et al, 2004;Stewart-Savage et al, 2001;Stewart-Savage and Yund, 1997), placentation (Zaniolo et al, 1987), germ cell recognition and migration (Ballarin et al, 2011;Brown et al, 2009;Rinkevich et al, 2013;Rosner et al, 2013;Sabbadin and Zaniolo, 1979).…”
Section: Self-and Cross-fertilization In B Schlosserimentioning
confidence: 99%
“…By combining previous classification schemes for botryllid ascidians (Ballarin et al, 2011; Ballarin and Cima, 2005; Cima et al, 2002; Hirose et al, 2003), we propose a generalized classification of B . leachii circulatory haemocytes into five functional groups: undifferentiated cells, immunocytes, mast cell-like cells, transport cells and storage cells (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…We additionally characterised the morphological and haematological modulation of injured colonies throughout WBR. Morula cells are known constituents of the immune system involved in inflammatory responses, haemolymph clotting, homeostasis, and tunic repair (Ballarin et al, 2011, 2001; de Leo, 1992; Menin et al, 2005). The large number of infiltrated morula cells observed during stage 1 of WBR highlights a need for both clearance of decaying or foreign debris and reorganization of the injured vascular system during the first 15 h post dissection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation